Kualitas Pelayanan Publik dalam Penerbitan Persetujuan Bangunan Gedung di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu - Yanto Heryanto; Moh. Sutarjo; Resa Ramadhani (Jurnal Syntax Transformation, 2023)
This research title is “Public Service Quality in Issuing Building Approval at the Office of Investment and One Stop Integrated Services, Cirebon Regency. So far, the public’s mind that PBG services seem complicated and convoluted, old services and less than optimal. Therefore, the formulation of the problem in this study is how the quality of PBG publishing services, what factors contribute to PBG issuance and what effort need to made to optimize PBG publishing services at DPMPSTP Cirebon Regency. This research uses qualitative research with a descriptive approach. Data collection techniques used interview, observation and documentation techniques used interview, observation and documentation techniques in the form documents and archives related to the quality of PBG services at DPMPTSP Cirebon Regency. The conclusion of the study is that PBG services at DPMPTSP Cirebon Regency have been going well although there are still some things that are not optimal and need to be improved. Researchers suggest that the services provided by DPMPTSP Cirebon Regency must be more professional, effective, efficient and the existing deficiencied need to be improved so that optimal.